A Conceptual Model of Madrasah Leadership Based on Neuroleadership and Whole Brain Management - Rudiana Rudiana (AIM: Journal of Islamic Education Management, 2026)
The excellence of 21st-century madrasahs is no longer determined solely by capital, infrastructure, technology, or management, but by the ability to optimize human resources’ cognitive abilities, creativity, knowledge, and collaboration through neuroleadership. This study aims to formulate a conceptual model of madrasah leadership based on neuroleadership to support the holistic management of brain potential. The study employs a qualitative approach using a descriptive-analytical literature review method. Data were sourced from reputable scientific articles, books on educational neuroscience, modern leadership theories, national education policies, and international research on neuroleadership. Data were analyzed using content analysis through concept identification, perspective synthesis, and conceptual model construction. The results indicate that madrasah excellence requires fifth-generation management that prioritizes knowledge-based activities, learning competencies, an understanding of how the brain works, and the optimization of cognitive potential as its primary foundations. The principle of whole-brain management helps leaders recognize diverse thinking patterns, integrate cognitive preferences, and align individual thinking tendencies with job requirements. The application of neuroleadership strengthens motivation, learning, social interaction, collaboration, innovation, and organizational performance. Thus, neuroleadership is a strategic competency for madrasah leaders to build governance that is adaptive, collaborative, innovative, people-oriented, and sustainable. This model underscores the importance of developing leaders who can effectively manage cognitive diversity as a collective strength of the madrasah in the face of complex and dynamic changes in education